Physiotherapeutic resources for pre and post-operative treatment of uterine prolapse (Research, Society and Development, 2024)
Introduction: Uterine prolapse is a condition characterized by the displacement of the uterus from its usual position, descending towards the vagina due to the weakening of the muscles and ligaments that support it. It affects up to 50% of women who have given birth, with 14% to 19% of women undergoing surgical correction. Objective: To analyze physiotherapeutic resources for the pre- and postoperative treatment of uterine prolapse. Methodology: Systematic and descriptive study type, collection of SciELO and LILACS databases, PEDro covering the period from 2015 to 2024. Results: 44 titles were found, of which 10 articles corresponded to the previously established inclusion criteria, 05 PEDro, 03 from LILACS and 02 from SciELO, of these studies, 2 are of the randomized controlled clinical trial type, 2 are randomized controlled studies, 1 retrospective cohort, 1 Pelvic Organ Prolapse/Incontinence Sexual Questonnaire-IUGA Revised (PISQ-IR) questionnaire, 1 clinical study, 1 case study, 1 cross-sectional study and 1 prospective observational study, 4 were published in English, and 6 in Portuguese, addressing physiotherapeutic resources for the pre- and postoperative treatment of uterine prolapse. Conclusion: It is concluded that studies specifically aimed at the treatment of uterine prolapse are scarce, however, through the literature evidenced on Pelvic Organ Prolapse and complications such as urinary incontinence, it is possible to understand how physiotherapy interventions can influence recovery in the pre- and post-operative periods in a positive and effective way.